2016
DOI: 10.1080/0886022x.2016.1207052
|View full text |Cite
|
Sign up to set email alerts
|

Xuezhikang ameliorates contrast media-induced nephropathy in rats via suppression of oxidative stress, inflammatory responses and apoptosis

Abstract: Background: The aim of this study was to assess the preventive effect of xuezhikang (XZK) to replace atorvastatin on the contrast media-induced acute kidney injury (CI-AKI). Methods: The male Sprague-Dawley rats were divided into five groups: group 1 (sham), injected with normal saline; group 2 (XZK), treated with XZK; group 3 contrast media (CM), injected with CM; group 4 (CM þ ATO), injected with CM þ pretreatment with atorvastatin; group 5 (CM þ XZK), injected with CM þ pretreatment with XZK. Twenty-four ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The apoptotic markers were also reduced [29][30][31][32][33][34]. Furthermore, an appearance of unfavorable histological findings was decreased in an ischemic-reperfusion injury model [29][30][31][32][33][34]. These findings suggested that statins and probucol could attenuate CIN by modulation of NO, inflammatory responses, oxidative stress and apoptotic processes, leading to improved renal function [29][30][31][32][33][34].…”
Section: Lipid-lowering Agents As Interventions To Reduce Cinmentioning
confidence: 82%
See 2 more Smart Citations
“…The apoptotic markers were also reduced [29][30][31][32][33][34]. Furthermore, an appearance of unfavorable histological findings was decreased in an ischemic-reperfusion injury model [29][30][31][32][33][34]. These findings suggested that statins and probucol could attenuate CIN by modulation of NO, inflammatory responses, oxidative stress and apoptotic processes, leading to improved renal function [29][30][31][32][33][34].…”
Section: Lipid-lowering Agents As Interventions To Reduce Cinmentioning
confidence: 82%
“…Lipid-lowering agents including rosuvastatin, [30,31] simvastatin, [31,32] atorvastatin, [31,33] xuezhikang (containing lovastatin), [33] and probucol [34] were investigated as potential pharmacological interventions in CIN animal models. These interventions appeared to effectively attenuate CIN as indicated by decreased level of kidney thiobarbiturates (TBARS), serum or renal MDA, serum protein carbonyl content (PCC), and increased serum thiol and glutathione (GSH) [29][30][31][32][33][34]. Inflammatory markers were also ameliorated as indicated by reduced IL-6, TNF-α, monocyte chemotactic protein-1 (MCP-1), myeloperoxidase (MPO), and increased NO [29][30][31][32][33][34].…”
Section: Lipid-lowering Agents As Interventions To Reduce Cinmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, interest has been raised for the use of NAC in the prevention of cisplatin induced oto- and nephrotoxicity. Interestingly, CIN from iodine-based contrast agents and cisplatin share common mechanistic features including both intrinsic cellular- and inflammation-related ROS mediated cellular and stromal peroxidation damage [ 15 20 ]. The following properties of NAC are hypothesized to be paramount for the prevention of oto- and nephrotoxicity: (1) NAC is thought to act as a vasodilator through nitric oxide effects, thus improving blood flow, (2) NAC is a precursor to GSH, the body’s endogenous ROS scavenger, (3) the antioxidant properties of NAC dampen inflammation caused by damage-associated molecular patterns that arise from biological macromolecule peroxidation by ROS and cellular necrosis, and (4) NAC prohibits apoptosis and promotes cell survival by the activation of an extracellular signal-regulated kinase pathway [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several studies have discovered the antioxidant active constituents from natural plant extracts that could ameliorate CM-induced nephropathy in rats. These agents include magnolin [25], curcumin [7], and xuezhikang [26]. Recently, our previous study showed that pre-treatment with PE extract exhibited the antioxidant effect in CI-AKI rats as shown by the improvement of the oxidative-status parameters including lower renal malondialdehyde, higher renal Total antioxidant capacity (TAC), Superoxide dismutase (SOD) and catalase (CAT) activity, the improved renal function, and the attenuation of the severity of pathological damage [22].…”
Section: Discussionmentioning
confidence: 99%